Analysis of trends in usage of analgesics and sedatives in intensive care units of South Korea: A retrospective nationwide population-based study. Issue 35 (August 2018) - Kim, Hyuk-Hoon; Choi, Sang Chun; Ahn, Jung Hwan; Chae, Minjung Kathy; Heo, Jaesung; Min, Young-Gi
Abstract : Abstract: The use of analgesics and sedatives plays an important role in improving patient outcomes in the intensive care unit (ICU). Various drugs exist, each with associated differences in patient outcomes; therefore, critical and intensive care medicine societies have developed guidelines for usage of analgesics and sedatives for improved patient outcomes. However, studies investigating drug use in the ICU have been based on surveys administered to medical staff, without accurate insight into the drug use based on prescriptions and behaviors of ICU medical staff, thus failing to demonstrate the actual status of the implementation of these guidelines into clinical practice. Using data from the Health Insurance Review and Assessment Service in South Korea, we analyzed the current use of analgesics and sedatives in ICUs nationally. In addition, we compared the use of analgesics and sedatives in the ICU based on the latest guidelines. We performed a nationwide retrospective study using data available in the Health Insurance Review and Assessment Service database. We included 779, 985 patients who had been admitted to the ICU from January 1, 2010, to December 31, 2014. Descriptive statistics were calculated to analyze the type and frequency of analgesic and sedative use in the ICU, using drug codes for analgesics and sedatives commonly prescribed in the ICU. The most commonly used analgesics and sedatives for all patients admitted to the ICU were pethidine (26.14%) and midazolam (32.18%), respectively. Sedatives and analgesics were more commonly used in mechanically ventilated patients. Among analgesics, the usage rate of pethidine and morphine decreased, whereas the usage rate of fentanyl and remifentanil increased. Among sedatives, the usage rate of benzodiazepine decreased, whereas the usage rate of propofol increased. There was discordance between current usage of analgesics and sedatives and the recommended usage stipulated by ICU guidelines. However, the trend of drug usage is changing to match the guidelines, which recommend maintenance of light sedation using an analgesia-based regimen and usage of short-acting drugs for routine monitoring of pain, agitation, and delirium in ICU care.